Pengembangan Aplikasi Web Pengelolaan Alokasi Dana Desa Dengan Model Prototyping - Erfina Latuconsina; Bayu Priyambadha; Herman Tolle (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In order to improve service and welfare of the community, a village has the right to obtain a portion of the central and regional financial funds received by the district called Alokasi Dana Desa (ADD) which is channeled through Village / Village Cash. However, the government did not get information about financial management in the village and asked for funds with inappropriate financial statements that confused financial supervisors in government offices. Therefore this research was conducted with the aim of facilitating the supervision process of the use of village funds, with the support and development of a web-based reporting system for financial oversight of the supervision of village funds, because all financial reports, funds usage reports and village activities will be entered into the website supervision of village funds and can be directly checked by the financial supervisor. In this study using the prototyping software development model, and bootstrap framework, and using jquery and javascript in making the display system more interactive. Testing this system uses the white box method and black box testing for functional testing, and compatibility testing methods for non-functional testing. The results of testing on 45 Functionalities in the management application for village fund allocation obtained 100% valid results, the system can be run on two different browsers on Google Chrome and Mozilla Firefox.